First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations HONORARY ORGANISER'S REPORT THROUGH lack of knowledge, the people of this country are dying before their time from preventable disease. To propagate more widely the sources of information the People's League of Health was established as an additional limb of the already existing Educational Health bodies working in the service of the Nation. The League was founded in August, 1917, but it was not until April, 1919, that the Medical Council met for the first time to consider and discuss the best means of meeting the aims and objects of the League — that of raising the standard of health of the British Nation. They were in session at intervals during that entire year, and in January, 1920, the inaugural Meeting at Claridge's Hotel was held, under the Chairmanship of Viscount Burnham, one of the Vice-Presidents of the League. The Hon. Francis N. Curzon was invited to act as Hon. Treasurer, Messrs. Edward Moore & Son as Hon. Auditors, Messrs. Fladgate & Son as Hon. Solicitors to the League. An account was opened in the name of the League at the London County, Westminster & Parr's Bank. The Finance Committee was called into being immediately after. In April of the same year, the Lay Council and Recreation and Entertainment Committee met for the first time, and the League became a living entity. These years have been pioneer years of effort with one thought always before us — a Healthy Nation is a Happy Nation. The King's Interest. In July, 1920, His Most Gracious Majesty The King honoured the Founders, Vice-Presidents and Official Members by becoming the Patron of the League. In December of the same year it was His Majesty's pleasure to become the Royal Founder of the League. H.R.H. The Prince of Wales. In the early part of the year 1920, H.R.H. the Prince of Wales was asked to be graciously pleased to accept the office of President of the League, but His Royal Highness was not able to grant our request. The Presidency still remains vacant. In view of the great importance of the work undertaken by the League, and the knowledge that the League's power for good would be greatly enhanced by His Royal Highness's acceptance of this office, it is hoped that the Prince will, on his return to this country, find it possible to graciously comply with what is the earnest wish of every official member of the People's League of Health. The work of the League has been to lay before the people of this country the great truth that Health is Nature's greatest gift to Humanity, and that in the final struggle for existence, it is the nation which is the healthiest that will survive. We have endeavoured to arrest the attention of those in authority, and to gain the confidence of other sections of the public in the work undertaken by the League which is limitless in its scope, and of the utmost value. The League has constantly urged the need of preventative measures in relation to the health of the people of our country — Research and Educational. We have dwelt upon the fact that Hundreds of Thousands of pounds are spent annually in support of defectives, and in comparison how few pounds for the dissemination of the saving knowledge which might prevent defectiveness. To the voters and taxpayers of the country we have pointed out that what a government and human society does not spend on adequate housing and education and protection of its workers it pays in hundredfold amounts to Hospitals, Prisons, Workhouses, Asylums, Homes for the Feebleminded, Epileptics and Cripples, and that both from an economic and humanitarian point of view it is our duty to cut off the supply of patients 28 200/B/3/2/C693/1/71